AN EXPLORATORY STUDY ON THE HOUSING NEEDS OF SINGLE WOMEN IN PRE-OLD AGE -A CASE STUDY OF TAINAN, TAIWAN - Kan-Chung Huang; Linda Lin-Chin Lin; Jo-Hua Chiu; Mei-Chih Sung; Mei-Shu Wu (Graduate Program of Universitas Tarumanagara, 2025)
Taiwan is set to enter a super-aged society by 2025, and the proportion of single-person households is gradually increasing—particularly among never-married, single women living alone. As the aging population grows, some prior studies have explored topics such as housing arrangements and intergenerational support for older adults. However, research on the housing choices of older individuals living alone remains limited. Most elderly people in Taiwan live in homes over 30 years old, and the combination of aging individuals and aging buildings often creates a form of